2014
DOI: 10.1007/s11255-014-0843-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between lipid metabolism gene polymorphisms and nephropathy in type 2 diabetes: a meta-analysis

Abstract: Our meta-analysis supports that the ApoE ε2 allele and ACACB rs2268388 C>T might act as promotion factors of nephropathy in type 2 diabetes, whereas PPARγ rs1801282 C>G is a promising candidate genetic variation for reducing susceptibility to T2DN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
(68 reference statements)
1
8
1
Order By: Relevance
“…It is the authors’ opinion that different ethnic origins may have different effects on the correlation between PPARG Pro12Ala and CKD. Our study found that there was no significant correlation between PPARG Pro12Ala and CKD in the Caucasian sample, whereas results in previous meta-analyses indicated that the PPARG Pro12Ala dominant model has a significant protective effect against CKD [ 32 , 33 , 34 , 37 , 38 , 39 ]. One possible explanation for this is that our study excluded publications with incomplete genetic information, and precisely these excluded studies suggested that PPARG Pro12Ala has a significant protective effect against CKD ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…It is the authors’ opinion that different ethnic origins may have different effects on the correlation between PPARG Pro12Ala and CKD. Our study found that there was no significant correlation between PPARG Pro12Ala and CKD in the Caucasian sample, whereas results in previous meta-analyses indicated that the PPARG Pro12Ala dominant model has a significant protective effect against CKD [ 32 , 33 , 34 , 37 , 38 , 39 ]. One possible explanation for this is that our study excluded publications with incomplete genetic information, and precisely these excluded studies suggested that PPARG Pro12Ala has a significant protective effect against CKD ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, our case-control study found that there is no significant correlation between PPARG Pro12Ala and ESRD; this is consistent with the findings published in most previous observations pertaining to Asian populations [ 27 , 38 , 44 , 45 , 63 , 64 , 65 , 66 ]. To emphasize the level of evidence, our meta-analysis also indicated no significant correlation between PPARG Pro12Ala and CKD in the Asian sample; this was consistent with the results of previous meta-analyses for Asians [ 33 , 34 , 36 , 37 , 38 ]. However, no definite conclusions could be made from previous meta-analyses for Asians; therefore, TSA was used on our study to determine whether a definite conclusion can be obtained [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Researchers have found the strongest associations in Asian [9], including Chinese [8], and Caucasian populations by case-control studies [8, 9]. In a recent meta-analysis, Li et al [10] concluded that the T allele increases the susceptibility to T2DN. Functional in vitro studies have revealed that the activity of a DNA fragment containing rs2268388 was dramatically increased in proximal tubular epithelial cells (RPTECs), especially in T allele carriers [8].…”
Section: Lipid Metabolism-related Genesmentioning
confidence: 99%
“… 39 The rs1801282 C>G variant in PPARγ was closely associated with decreased DN risk. 40 However, further studies revealed that the PPARγ2 Ala12 variant provided renal protection by reducing the occurrence of albuminuria among patients with type 2 diabetes. 41 , 42 …”
Section: Nuclear Receptorsmentioning
confidence: 99%